Shiga toxigenic and enteropathogenic Escherichia coli in water and fish from pay-to-fish ponds - Ribeiro, L. F. [UNESP]; Barbosa, M. M.C.; de Rezende Pinto, F.; Guariz, C. S.L. [UNESP]; Maluta, R. P.; Rossi, J. R. [UNESP]; Rossi, G. A.M. [UNESP]; Lemos, M. V.F. [UNESP]; do Amaral, L. A. [UNESP] (Oxford University Press (OUP), 2016)
Escherichia coli is part of the normal microflora of the intestines of mammals. However, among the enteric pathogens, it is one of the leading causes of intestinal diseases, especially Shiga toxigenic E. coli, which can cause diarrhoea, haemorrhagic colitis and complications like haemolytic uraemic syndrome and thrombotic thrombocytopaenic purpura. Escherichia coli is considered a serious public health problem. Water and fish samples were subjected to biochemical tests to confirm the presence of E. coli and by PCR to verify the presence of pathogenic strains (O157, enteropathogenic and shiga toxigenic) in water and fish (skin, gastrointestinal tract and muscles) from pay-to-fish ponds located in the Córrego Rico watershed in the northeastern region of the state of São Paulo, Brazil. Of the 115 E. coli isolates from fish or water, five (4·34%) contained eae and stx2 genes, one had only the eae gene and two had the stx1 gene. An isolate containing the stx2 gene was also found in the water sample. In addition, eight isolates (6·95%) from the fish gastrointestinal tract contained rfbEO157:H7 (O157 gene), and three (2·61%) contained stx2 and eae genes, demonstrating the potential risk to the environment and public health. The results provide useful basic information for the proper management of these environments and animals in order to prevent faecal pollution, reducing health risks to the Brazilian population.
Keywords: Enteropathogenic E. coli; Environmental; Oreochromis niloticus; Shiga toxigenic E. coli; Water